MASA DEPAN PENDIDIKAN ISLAM - Mawardi, Hasan (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2023)
This article discusses the past, present and future of Islamic education. Indonesia has a distinctive and unique education system called pesantren which has proven successful in producing many educational intellectual figures and models of character education. During the colonial period, Islamic boarding schools faced the Dutch and Japanese colonialists and carried out resistance movements to expel the colonialists. This is the problem and this is the response given by the Islamic boarding school. Towards independence, the Islamic boarding school students were again involved in formulating the Constitution as an urgent need at that time. During the New Order era, there were many madrasas that sprang up along with the birth of the SKB 3 Ministerial Decree Law Number 2/1989 concerning the National Education System. This was done as a response to discrimination against Islamic education. The struggle of Muslims continued until every student was obliged to receive religious education in accordance with the religion he adhered to and given by teachers of the same religion as them, then several State Islamic Universities were established in various provinces and Islamic boarding schools were recognized as part of the national education system. As a universal teaching in the sense that it is suitable for every place and age, Islamic education must color all aspects of life and provide answers to every problem of the times. For this reason, now several Islamic tertiary institutions exist with several faculties and study programs that usually can only be found on public campuses. A consistent step upholding the principle of